2013
DOI: 10.1108/dat-05-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and perceptions of recovery in Scotland: a qualitative study of injecting drug users attending methadone treatment

Abstract: Many researchers and service providers are looking to writings on recovery capital to give them some insight into how to deliver and design services that better respond to the needs of those seeking treatment. In this study we sought to understand what impact being a mother had on recovery. Using the recovery capital model we tracked the progress of mothers entering treatment with and without their children. Our study suggests that being a mother in recovery sets you apart from non-mothers in a number of ways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…Stigma is a cross-cutting concept that permeated all levels of the SEM and was referred to either directly or indirectly in 22 of the 37 included studies. The studies showed that service users are vulnerable to experiencing stigma from a wide range of sources including from pharmacy staff and other customers when collecting OST medications (44,(47)(48)(49)(50); the GP surgery and other healthcare settings (21,43,45,50,51); from their family and friends (25); from the wider community (25,27,29,41,43,45) and from the government (27,50).…”
Section: Stigmamentioning
confidence: 99%
See 4 more Smart Citations
“…Stigma is a cross-cutting concept that permeated all levels of the SEM and was referred to either directly or indirectly in 22 of the 37 included studies. The studies showed that service users are vulnerable to experiencing stigma from a wide range of sources including from pharmacy staff and other customers when collecting OST medications (44,(47)(48)(49)(50); the GP surgery and other healthcare settings (21,43,45,50,51); from their family and friends (25); from the wider community (25,27,29,41,43,45) and from the government (27,50).…”
Section: Stigmamentioning
confidence: 99%
“…This may leave service users vulnerable to relapse and overdose and may prevent them from seeking help from professionals for other health issues (21,43,51). Experiencing stigma can lead to feelings of shame and result in self-stigma -the lowering of one's expectations of self and motivation to change (25,30,50). Self-stigma may also be the driver of service users isolating themselves from others, which perpetuates feelings of exclusion and loneliness 45 The pharmacy setting appears to be a particularly strong source of stigma for OST service users; across several studies they reported feeling shame and embarrassment at the way they are looked at by other customers whilst collecting OST medications (43,44,47,49,50…”
Section: Stigmamentioning
confidence: 99%
See 3 more Smart Citations